Pengaruh Motivasi Bisnis Serta Program Pelatihan Terhadap Capaian Kinerja Penjualan Member Halal Network International – PT Herba Penawar Alwahida Indonesia (HNI-HPAI) - Syaikhu, Ahmad; Gustiawan, Deni; Saifudin, Asep (Jurnal Doktor Manajemen (JDM), 2024)
This study discusses the correlation between business motivation and training programs on the sales performance of members of Halal Network International - PT Herba Penawar Alwahida Indonesia (HNI-HPAI) as one of the Multi-Level Marketing (MLM) companies in Indonesia. Using indicators based on context, content, and process theory, this study seeks to understand how strong business motivation affects sales performance. This research also uses the training program evaluation method introduced by Kirkpatrick in 1967 to determine how the influence of training programs can impact sales performance. To find out these two things, the researcher distributed questionnaires and processed the data obtained by applying Structural Equation Modeling (SEM) using Smart PLS statistical software. The data analysis showed that motivation and training programs had a positive and significant effect on the sales performance of HNI-HPAI members.